Translating the Legal Terms in to Kurdish: Problem and Solution - Abdulwahid Musheer Mahmood; Awat Ahmed Muhamed Salih; Khabat Hadi Jameel (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Terminology is the science that investigates the relationship between the scientific concepts and the linguistic expressions. The title of this paper is (Translating the legal terms in to Kurdish: Problem and Solution). This work points out that translating terms into Kurdish has an important nationalistic and patriotic significance. Additionally, it has a crucial role for strengthening the status of the government, social relationships, policy, and united language. Thus, it’s a national and patriotic duty. The aim of this work is translating the legal terms into Kurdish with the issues that arise and furthermore, it elaborates the issues that arise amidst translating the terms. It’s hypothesized that problems will arise when composing the legal terms. The work clarifies the problems and suggests solutions for composing or deriving them. This work is answering the questions: What are the factors of linguistically weak legal terms? Are there problems when composing legal terms in Kurdish language? How do the problems of composing legal terms in Kurdish language can be resolved? This paper is consisted of two sections besides the introduction and the conclusion: The first section is specialized to terminology and composing terms in Kurdish. The second section is dedicated to setting legal terms, its problems and solutions, consisting of these headings: Composing terms in Kurdish language, The basic beliefs of composing terms, the problems of composing terms, the solutions of composing legal terms. And, the conclusion with abstract in Arabic and English Languages.